Analysis of Human Resource Development in Supporting Worker Productivity of PT. Tambang Bumi Sulawesi (TBS) - Basmala Septian Jaya; Abdul Razak; Nofal Supriaddin (Maneggio, 2025)
This research aims to find out and analyze: Human resource development in supporting Productivity at PT. Bumi Mine Sulawesi. The benefit of this study is that for the development of science, the results of this research are expected to add information and treasures about human resource development strategies in supporting worker productivity at PT. Sulawesi Earth Mine, a contribution of thought and as input material to support the basis of similar and relevant research theories. This research uses a descriptive qualitative method. Data was collected by means of observation, interviews.  The results of the study are that: (1) Human resource development at PT. Tambang Bumi Sulawesi (TBS) with training that is carried out every time there is a new product or program from the company's management, (2) PT. Tambang Bumi Sulawesi (TBS) organizes additional education and refresher education to increase cooperation between workers, and (3) In increasing Work Productivity at PT. Tambang Bumi Sulawesi (TBS) Every worker must analyze the work and master their respective jobdesks.